Intravenous Lipid Emulsion Entraps Amitriptyline into Plasma and Can Lower its Brain Concentration – An Experimental Intoxication Study in Pigs. (29th May 2013) - Heinonen, Juho A.; Litonius, Erik; Backman, Janne T.; Neuvonen, Pertti J.; Rosenberg, Per H.
Abstract: Intravenous lipid emulsion has been suggested as treatment for severe intoxications caused by lipophilic drugs, including tricyclic antidepressants. We investigated the effect of lipid infusion on plasma and tissue concentrations of amitriptyline and haemodynamic recovery, when lipid was given after amitriptyline distribution into well‐perfused organs. Twenty anaesthetized pigs received amitriptyline intravenously 10 mg/kg for 15 min. Thirty minutes later, in random fashion, 20% Intralipid ® (Lipid group) or Ringer's acetate (Control group) was infused 1.5 ml/kg for 1 min. followed by 0.25 ml/kg/min. for 29 min. Arterial and venous plasma amitriptyline concentrations and haemodynamics were followed till 75 min. after amitriptyline infusion. Then, frontal brain and heart apex samples were taken for amitriptyline measurements. Arterial plasma total amitriptyline concentrations were higher in the Lipid than in the Control group ( p < 0.03) from 20 min. on after the start of the treatment infusions. Lipid emulsion reduced brain amitriptyline concentration by 25% ( p = 0.038) and amitriptyline concentration ratios brain/arterial plasma ( p = 0.016) and heart/arterial plasma ( p = 0.011). There were no differences in ECG parameters and no severe cardiac arrhythmias occurred. Two pigs developed severe hypotension during the lipid infusion and were given adrenaline. In conclusion, lipid infusion, given not earlier than after an initial amitriptyline tissue distribution, was able to entrap amitriptyline back into plasma from brain and possibly from other highly perfused, lipid‐rich tissues. In spite of the entrapment, there was no difference in haemodynamics between the groups.